The media narrative as an object of discourse analysis - Yavinskaya, Yuliya V. (Journal of the Belarusian State University. Journalism, 2019)
Тhe article discusses theoretical approaches to narrative narrative in the media as the object of discourse analysis. In the first case, the narrative in the media discourse is considered as a theme (topic) – a formula structure loaded with certain values and ideology. In the second – as an event created on the basis of ideological and axiogenic properties of the referential event. The first approach provides examples of research on narrative deconstruction in media-oriented types of discourse (political, advertising, etc.) based on the corpus of phraseological units; slogans and ideological narratives, headlines and headings, advertising concepts and PR-messages, proverbial axiogenic events, typical plot situations, etc. In General, this approach can be called system-functional, expressing a universal narrative strategy of «folding» (involutio). In the second case, the researchers are interested in the event-driven nature of the narrative – both in the structuralist and poststructuralist aspects. In this case, the narrative is considered as a text event created according to a certain scheme on the basis of a reference event. The study narrative as an event dates back to the traditions of structural analysis and classical narrative analysis of the plot. The article provides examples of research advertising narratives and descriptive and narrative analysis (event-driven) component in the media texts, through language means of expression of facts, estimates, and descriptions; metanarrative as technologies of creation of «soft» news with the use of special narrative strategies. The fact that the event as localized in some human (individual or public) sphere is separately noted in the article. This approach to the narrative can be generally characterized as functional-analytical. It correlated with the narrative strategy of deployment (evolutio) as the transformation of «finite formulas» in the original semantic figures. In conclusion, in the media-oriented discourses (political, advertising, network) there is a process of narrativization, which indicates the disintegration of traditional media values (based on the principles of reflection of facts in the form of an inverted pyramid model). This conclusion, in General, corresponds to the description of the processes of media transformation of reality.